2002
DOI: 10.1074/jbc.m110891200
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Function of AP-1 Transcription Complexes during Muscle Cell Differentiation

Abstract: The role of activating protein-1 (AP-1) in muscle cells is currently equivocal. While some studies propose that AP-1 is inhibitory for myogenesis, others implicate a positive role in this process. We tested whether this variation may be due to different properties of the AP-1 subunit composition in differentiating cells. Using Western analysis we show that c-Jun, Fra-2, and JunD are expressed throughout the time course of differentiation. Phosphatase assays indicate that JunD and Fra-2 are phosphorylated in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 39 publications
(48 reference statements)
5
65
1
Order By: Relevance
“…Early up-regulation of the AP-1 transcription factors c-jun, c-fos, and junB has been described after cardiac hypertrophic stimuli (Parker and Schneider 1991). The AP-1 member junD, although dispensable in development (Thepot et al 2000), has been shown to be involved in muscle cell differentiation (Andreucci et al 2002). Interestingly, junD is specifically expressed in the developing heart and cardiovascular system (Thepot et al 2000).…”
mentioning
confidence: 99%
“…Early up-regulation of the AP-1 transcription factors c-jun, c-fos, and junB has been described after cardiac hypertrophic stimuli (Parker and Schneider 1991). The AP-1 member junD, although dispensable in development (Thepot et al 2000), has been shown to be involved in muscle cell differentiation (Andreucci et al 2002). Interestingly, junD is specifically expressed in the developing heart and cardiovascular system (Thepot et al 2000).…”
mentioning
confidence: 99%
“…Additionally, the Fra-2-c-Jun heterodimer is one of the main AP-1 binding complexes present in C2C12 differentiation (Andreucci et al, (25) regulaƟon of B cell apoptoƟc process (9) regulaƟon of leukocyte migraƟon (21) acƟn filament organizaƟon (29) posiƟve regulaƟon of apoptoƟc signaling pathway (24) negaƟve regulaƟon of cysteine-type endopepƟdase acƟvity (16) negaƟve regulaƟon of cysteine-type endopepƟdase acƟvity involved in apoptoƟc process (16) regulaƟon of myeloid cell differenƟaƟon (42) acƟn filament-based process (71) 2002). Fra-2 is present in different isoforms and subject to posttranslational modification by ERK (Alli et al, 2013;Andreucci et al, 2002). To date, Fra-2 ChIP-seq data is not available.…”
Section: Resultsmentioning
confidence: 99%
“…4D,E). As we previously showed, c-Jun and Fra2 function as a heterodimer in skeletal muscle (Andreucci et al, 2002), therefore this disparity could be related to the relative transcriptional potency of these transcription factors: cJun is a robust transcriptional regulator and can form a homodimer in the absence of Fra-2, whereas Fra-2 is a weaker transcriptional activator that has no intrinsic transactivation domain and relies on recruitment of the Jun heterodimeric partner for bringing transactivation properties to the AP-1 complex (Suzuki et al, 1991;Wisdon and Verma, 1993). Together, these data indicate the possibility of antagonistic regulation of Hspb7 by AP-1 and MEF2.…”
Section: Mef2a and C-jun And Fra-2 Regulate Atrophy-induced Hspb7 Expmentioning
confidence: 99%
“…Recent studies have shown that over-expression of ATF-2 increases the proliferation in human and mouse cancer cells [10,11]. Again, in studies performed, it is suggested that over-expression of Fra-2 is associated with the phenotype of aggressive tumour at some cancers and may be related to the progress of some cancer types and Fos-related antigen-2 (Fra-2) is showed to be an important AP-1 transcription factor in differentiating cells [4,8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Many cellular function take place depending on transcription factors [1][2][3]. AP-1 transcription complex functions in several cellular processes such as growth, proliferation, differentiation, apoptosis and oncogenic transformation [4]. AP-1 is an inducible transcription factor and consists of multiple protein complexes like many transcription factors [3,5].…”
Section: Introductionmentioning
confidence: 99%